PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD N 003 PERANAP KABUPATEN INDRAGIRI HULU - Misrawati Misrawati; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the low student learning outcomes in science subjects with an average value of 59.8, there are still many students who value below a predetermined KKM school is 70, is affected by many factors, among others: a) Less active students follow the lessons, because students are less interested in how the presentation of the material that much centered on teachers who use the lecture method. b) Lack of opportunity to interact between teachers and students, c) Lack of student motivation in conveying the idea, because the teacher is not giving reinforcement to students who dared to express his opinion. Solving the problem with the use of cooperative learning. Solving the problem with the use of cooperative learning. Applying cooperative learning model, learning model by assigning student groups attract, train and train remedy issue an opinion for the good cooperation. This research aims to improve learning outcomes IPA Elementary School fourth grade students 003 Peranap the academic year 2014/2015. The subject is a fourth grade primary school students 003 Peranap the number of students as many as 20 students. This research is a form of action research with two cycles. The research data show that the learning outcomes of students has increased, the value of acquired activities of teachers in the first cycle with the average was 72.32% and the second cycle increased by an average of 90.18% of students in the first cycle of activity with an average of 69.31% and the second cycle increased by an average of 90.18%. Research data has increased which before the action model of cooperative learning on the base score of complete 3 people tuntasdan 17 people who did not complete the average value of 59.8 the first cycle increased the number of students 20 people, with an average value 71dan cycle II nliai amount to an average of 81 can thus be concluded that the hypothesis in this study is